Seaweed Investment as Application in Development of Minapolitan Area - Caroline, Caroline (Jurnal Ekonomi Pembangunan: Kajian Masalah Ekonomi dan Pembangunan, 2013)
Consequences of regional autonomy is not easy, this is because a required area should look for alternative sources of financing regional. One of the sources of financing in the Brebes district is the development of seaweed cultivation to be exported to other countries. The calculations show that the investment in seaweed farming is feasible to be developed because of the many advantages gained than seaweed farming. The first advantage of the presence of a source of income for local communities and Brebes district, opening job opportunities broadly, to develop products made from seaweed such as cosmetics, pharmaceuticals, herbs, jelly, and so forth.